Avaliação in vitro da atividade carrapaticida da Turnera subulata Sm. e associação com acaricida químico - Farias, Michelle Vanessa Soares de (2015)
The cattle is the main host for Rhipicephalus (Boophilus) microplus, is an important ectoparasite of wide propagation in tropical and subtropical regions of the world. The manipulation of acaricide chemicals is the main available method at controlling the ticks, whose main disadvantage includes increasing parasite resistance to the active principle and the possibility of the presence of residues in animal products and environmental damage. Turnera subulata Sm. popularly known as chanana is an annual herb grown in sandy soils and slopes common in Northern and Northeast of Brazil. The chanana was tested as a dry extract and also associated with a chemical acaricide. Tests were conducted in dry ticks on absorbent paper and were wet after the dry extract immersion. Homogeneous groups of triplicates were separated, containing 10 ticks, obtaining decreasing concentrations of 50%, 25%, 12.5%, 6.38% of dry extract respectively, association with the pyrethroid and distilled water as negative control. The biocarrapaticidogramas variables were evaluated according to reproductive efficiency (RE), and product efficiency (PE) according to the equations presented by Drummond et al. (1973). Throughout this study, there was no death of engorged ticks at any concentration of the treated groups. There was effectiveness of the product on the hatching of eggs of females with dry extract of Turnera subulata Sm., however, the percentage presented in all concentrations are low for the control of infestation by ticks, we suggest that the combination extract to other plant that posseses active ingredients acaricide. The interactive effect of the dry extract chanana with pyrethroid did not present acceptable efficiency according to what is stated by the Ministry of Agriculture, probably a result of the indiscriminate use of the active principle of the pyrethroid class that generated a parasite resistance.